2005
DOI: 10.1007/s00198-005-1983-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of incidence of osteoporotic fractures in the female Spanish population older than 50

Abstract: It is well known that the adoption of preventive measures for osteoporosis may contribute to minimizing its impact as a result of bone fractures. However, there are well-recognized risk factors involved in the onset of osteoporosis that are not possible to modify. Better knowledge of these non-modifiable factors could aid prevention in subjects at high risk of fractures. The aim of this study was to evaluate the likely association between gynecological, reproductive and family history of hip fracture with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 24 publications
1
18
0
4
Order By: Relevance
“…However, over five dozen epidemiologic studies of pre-, peri-, and postmenopausal women have found a neutral effect (16,38,63,158,203,214,215,290,292,299,341,356,368,379,383,397,444,445,448,463,481,506,509,541,547,611,619,625,636,648,683,700,761,828,845,846,861,864,865,869,879,934,935,944,951,969,1020) or a protective effect (25,27,71,…”
Section: Human Datamentioning
confidence: 99%
“…However, over five dozen epidemiologic studies of pre-, peri-, and postmenopausal women have found a neutral effect (16,38,63,158,203,214,215,290,292,299,341,356,368,379,383,397,444,445,448,463,481,506,509,541,547,611,619,625,636,648,683,700,761,828,845,846,861,864,865,869,879,934,935,944,951,969,1020) or a protective effect (25,27,71,…”
Section: Human Datamentioning
confidence: 99%
“…For example, early age at menarche (AAM) is a risk factor for breast cancer [2][3][4] , cardiovascular disease [5] , depression [6] , eating disorders [7] , conduct and behavioral disorders [8] , diabetes [9] and increased all-cause mortality [10] . Conversely, late AAM is associated with a decreased risk of ischemic heart disease [11] but an increased risk of osteoporotic fracture [12,13] . Boys are also affected by alterations in pubertal timing, with delayed puberty being a cause of bullying, poor self-esteem and psychosocial distress, while early puberty is a risk factor for testicular cancer [8] .…”
Section: Introductionmentioning
confidence: 99%
“…The timing of menarche is determined by both genetic and environmental factors [1,2] . Results from previous studies have shown that a female's AAM affects her health later in life and has been identified as a risk factor for several traits including breast cancer [3,4] , osteoporotic fracture [5] , abnormal lung function [6] and depression [7,8] . Moreover, recent researches mentioned that earlier menarche has also been associated with obesity [9] , type 2 diabetes [10][11][12] as well as increased metabolic syndrome [13,14] , and all these confer an increased risk of cardiovascular disease (CVD).…”
Section: Introductionmentioning
confidence: 99%